2022
DOI: 10.1002/fsn3.2831
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and chemical characterizations of jujube (Ziziphus jujuba Mill.) to select superior accessions

Abstract: Although jujube (Ziziphus jujuba Mill., the Rhamnaceae family) is mainly adapted to temperate and subtropical regions and naturally to areas with cold winters and hot summers, it is widely distributed in dry climates (Gao et al., 2011). Jujube fruit is rich in vitamins A, B, and C, as well as minerals and various compounds such as alkaloids, flavonoids, sterols, tannins, saponins, and fatty acids. Jujube also has significant antioxidant properties that can neutralize the activity of free radicals, so its fruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…The total phenolic content (TPC), total flavonoid content (TFC), and total flavonol content (TFLC) of fermented jujube puree are presented in Table 2 , and commensurate findings of Khadivi & Beigi [ 26 ] and Ali et al [ 27 ]. The higher phytochemical concentrations in JLAP samples compared to JCON showed that lactic acid bacteria (LAB) and acetic acid bacteria (AAB) increased the phytochemical concentrations in the jujube puree during fermentation.…”
Section: Resultssupporting
confidence: 74%
“…The total phenolic content (TPC), total flavonoid content (TFC), and total flavonol content (TFLC) of fermented jujube puree are presented in Table 2 , and commensurate findings of Khadivi & Beigi [ 26 ] and Ali et al [ 27 ]. The higher phytochemical concentrations in JLAP samples compared to JCON showed that lactic acid bacteria (LAB) and acetic acid bacteria (AAB) increased the phytochemical concentrations in the jujube puree during fermentation.…”
Section: Resultssupporting
confidence: 74%
“…The findings of Xue et al (2021) have proven that the TPC and TFC of selected jujube varieties grown in Korea were around 0.359-1.041 mg per gram of fruit weight. In another study conducted on different accessions of jujube from the Tookean area in Lorestan province of Iran, the TPC ranged from 1.69-14.05 mg GAE/g fresh weight, and the TFC varied from 0.25-2.01 mg QE/g fresh weight (Khadivi & Beigi, 2022). In the study conducted to determine the TPC and TFC of eight Iranian jujube populations and imported jujube, the highest TPC and TFC were 32.902 mg GAE/g and 3.064 mg QE/g, respectively (Ghani et al, 2022) Azizi and Pirbodaghi (2016) have investigated the variations in TPC and TFC of fruit extracts among 29 jujube accessions originating from seven provinces of Iran.…”
Section: Discussionmentioning
confidence: 96%
“…This analysis determines the determination coefficient ( r 2 ), which shows the relationship between the morphological trait and the molecular marker (Roy et al, 2006 ). Also, MRA has been used to determine the relationships between morphological characters (Beigi & Khadivi, 2023 ; Khadivi et al, 2021 ; Khadivi & Beigi, 2022 ; Mirheidari et al, 2022 ; Mirmahdi & Khadivi, 2021 ; Zandiehvakili & Khadivi, 2021 ).…”
Section: Introductionmentioning
confidence: 99%